Tanggung Jawab Hukum Balai Harta Peninggalan dalam Menjalankan Penetapan Pengadilan terkait Afwezigheid atas Harta Peninggalan - Muhammad Zein Alby (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study examines the legal responsibility of the Public Trustee Office (Balai Harta Peninggalan, BHP) in implementing court determinations related to assets owned by individuals declared afwezigheid (absent). The main issue concerns how BHP manages, administers, and executes the sale of such assets within the limits of its statutory authority. The research aims to analyze the extent of BHP’s legal responsibility in safeguarding ownership rights while ensuring legal certainty in accordance with Indonesian civil law. This study applies a normative juridical method using statutory, conceptual, and analytical approaches based on primary and secondary legal materials. The findings show that BHP’s responsibilities are limited to administrative and representative functions, strictly bound by formal legal norms as stated in the Civil Code and the Ministerial Regulation No. 27 of 2013. The study concludes that the implementation of BHP’s authority must adhere to the principles of legality, accountability, and due process of law to prevent conflicts of interest and protect the rights of rightful heirs. This research contributes to strengthening the normative framework of public trusteeship in Indonesia’s civil law system.